PERUBAHAN SIFAT FISIK DAN STABILITAS DIMENSI KAYU AKIBAT PENGAWETAN MENGGUNAKAN IMPREGNASI KARBONDIOKSIDA (PERENNIAL, 2007)
The effect of preservative treatment using carbon dioxide as a carrier solvent on wood physical properties and dimensional stability had been observed on three commercial wood species (Agathis sp., Palaquium sp., and Heritiera sp.). For the purpose of the study, wood samples measuring 1,5 (R) x 1,5 (T) x 15 (L) cm were prepared. Treatment was conducted at elevated temperature (50C - 350C) and increased pressure (60 - 80 kgf/cm2) on one occasion with five replicates using two specimens of each wood species for each treatment. The final treatment condition was maintained for three different periods (10, 20, 30 minutes). Results indicated that the physical properties and dimensional stability of the preserved wood were not significantly affected by the application of CO2 impregnation as carrier solvent.Key words: Preservative treatment, Carbon dioxide, Carrier solvent, Wood physical properties, Wood dimensional stability